Edukacja osób niepełnosprawnych jako dobro wspólne na tle rozważań administracyjnoprawnych - Raszewska-Skałecka, Renata (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Education of people with disabilities, considered as acommon good, points out legal subjectivity of adisabled person, the right to education and educational duties in the educational system. From the perspective of the state and its administration education, understood as acommon good, means performance of educational tasks in the scope of special education for a disabled person.
Keywords: edukacja; osoby niepełnosprawne; dobro wspólne; podstawy administracyjnoprawne